Studi Bentuk dan Elemen Arsitektur Masjid di Jakarta dari Abad 18 - Abad 20 - Widya Katarina (Bina Nusantara University, 2012)
Modern and traditional mosques in Jakarta have differences triggered by the growing progress of time. Nevertheless, the basic elements of the mosques, such as a floor plan of the main room is square-shaped, do not change a lot. No matter what the forms are, the main function of a mosque is for praying. This study discusses about the forms of mosques in Jakarta from the 18th century - 20th century.